Lets Simplify Step by Step:
5(2x + 1) - 4
Distribute:
(5)(2x) + (5)(1) + -4
10x + 5 + -4
Combine Like Terms:
10x + 5 + -4
(10x) + (5 + -4)
10x + 1
Hence, Letter Choice, (C); 10x + 1 ===> 5(2x + 1) - 4
CHECK:
5(2x + 1) - 4 ====> 10x + 1 ===> True for all x ===> Both Sides Equal.
Steps:
5(2x + 1 ) - 4 = 10x + 1
Expand:
5(2x + 1 ) - 4 ====> 10x + 1
10x + 1 =====> 10x + 1
Subtract 1 from both sides:
10x + 1 - 1 =====> 10x + 1 - 1
Simplify:
10x = 10x
Subtract 10x form both sides:
10x - 10x = 10x - 10x
Simplify:
0 = 0
Therefore, when checked, 5(2x + 1 ) - 4 ===> 10x + 1, Which makes Both Sides Equal; True for All " x "
Have a great day : )